Efficacy of Anti-CD38 Monoclonal Antibodies for Relapsed or Refractory Multiple Myeloma in Stem Cell Transplant-Ineligible Patients Aged over 65 Years: A Propensity Score-Matched Study - Satoshi Yamasaki; Michitoshi Hashiguchi; Nao Yoshida-Sakai; Hiroto Jojima; Koichi Osaki; Takashi Okamura; Yutaka Imamura (Hematology Reports)
Background: The development of newer agents, including anti-CD38 monoclonal antibodies (mAbs), has significantly improved overall survival (OS) in patients with relapsed or refractory multiple myeloma (RRMM). However, the treatment of older patients with RRMM who are transplant-ineligible remains challenging. Methods: We retrospectively evaluated OS in 78 transplant-ineligible patients with RRMM who were aged ≥ 65 years and treated at our institution between February 2012 and November 2023. Results: Unadjusted OS was significantly longer in the anti-CD38 mAb-exposed group (i.e., those previously treated with daratumumab and receiving isatuximab plus pomalidomide and low-dose dexamethasone because of disease progression during treatment with daratumumab [n = 6], daratumumab plus pomalidomide and low-dose dexamethasone [n = 9], or isatuximab plus pomalidomide and low-dose dexamethasone without daratumumab-exposure [n = 14]) than in the anti-CD38 mAb-naïve group (no exposure to daratumumab or isatuximab [n = 49]) (p < 0.001). To address potential confounder factors associated with use or nonuse of anti-CD38 mAbs, we performed propensity score matching (PSM) using age, sex, performance status, and Geriatric 8 and Instrumental Activities of Daily Living scores. PSM identified 14 subjects from the anti-CD38 mAb-exposed group with baseline characteristics similar to those of 14 subjects from the anti-CD38 mAb-naïve group. After PSM, the adjusted OS was significantly longer in the anti-CD38 mAb-exposed group than in the anti-CD38 mAb-naïve group (p < 0.001). Conclusion: These findings provide insights into the optimal use of anti-CD38 mAbs in patients with RRMM who are transplant-ineligible and aged ≥65 years and on candidates who are appropriate for novel approaches, such as chimeric antigen receptor T-cell or bispecific T-cell engager therapy.